Sustainability Impact: A Representation of Social Enterprise Value - Anisa Kusumawardani; Fibriyani Nur Khairin; Ginting, Yoremia Lestari (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
Social enterprises have a unique characteristic in their business objectives, which is the element of profit as well as creating value that addresses social issues in society. In practice, the sustainability impact represents the value that shows how social enterprises establish strategies, conduct daily operations, and build partnerships with stakeholders. Therefore, this study aims to explore and understand the meaning of "impact" from the perspective of social enterprise actors. The research data consists of observations and interviews with social enterprise business actors, as well as documentation related to the research theme. Data analysis was conducted using a case study approach, which involves data reduction, coding, and theme determination, followed by interpreting the analysis results to address the research problem. The findings illustrate that the impact for social enterprises can be interpreted as creating positive changes in the lives of people in society. This is ingrained from the strategy setting to daily operations because success for a social enterprise is not only measured by profit but also by the social impact generated. Additionally, a social enterprise is also considered a green business when impact thinking correlates with sustainability principles.